(untitled) (American Journal of Research in Humanities and Social Sciences, 2024)
This article aims to support the activities of museums in our Country, complex development of their marketing policy and services sphere, effective application of innovative technologies to museums, as well as to create modern new expositions on the history of Uzbek people and statehood in museums, the first and Second Renaissance periods, the life and work of great allomas, to widely promote our rich historical and cultural heritage.